The effect of polychlorinated biphenyls on type 2 diabetes risk is mediated via DNA methylation - Kartiosuo, Noora; Auranen, Kari; Mansell, Toby; Novakovic, Boris; Nevalainen, Jaakko; Pahkala, Katja; Rovio, Suvi; Mykkänen, Juha; Viikari, Jorma; Juonala, Markus; Rantakokko, Panu; Kiviranta, Hannu; et al. (Elsevier Ltd, 2026)
Polychlorinated biphenyls (PCBs) have been identified as diabetogens and potential epigenetic regulators. Epigenetic variation is implicated in the pathogenesis of type 2 diabetes (T2D) and is therefore a potential mechanism linking PCB exposure and T2D. We here investigate the effect of PCB exposure on T2D risk and the extent to which this is mediated via DNA methylation (DNAm) using two epigenome-wide association studies and mediation analysis. Exposure to PCBs, especially congeners 74, 99, 118, 138 and 183, increased the risk of T2D (range of ORs 1.38-1.54). Five CpG sites were identified as potential mediators. Together, methylation at these sites was estimated to mediate 40 % (95 % CI: 20, 60 %) of the effect of PCBs on T2D. The strongest evidence was obtained for cg00574958, located in the first intron of the CPT1A gene. This study is among the largest to date assessing the link between PCBs and T2D, and the first to investigate the mediation by DNAm. The evidence for methylation at cg00574958 as a mediator of the PCB-T2D relationship supports the widely-replicated link of CPT1A DNA methylation to a range of metabolic phenotypes including obesity, dyslipidemia and T2D and indicates a possible future target for epigenetic intervention.